Reducing Preventable Readmissions in a Neurosurgical Patient Population at an Academic Medical Center. (1st September 2019) - Moosa, Shayan; Bowerman, Lindsay; Smith, Ellen; Bryant, Mindy; Krovetz, Natalie; Pritchett, Melissa; Staton, Nancy; Wilson, JoAnne; Wisinski, Carol; Bullock, Patty; Chen, Kearby; Prather, Susan; et al.
Abstract: INTRODUCTION: Hospital readmissions are extremely costly in terms of time and resources and negatively impact patient safety and satisfaction. In this study, we performed a Pareto analysis of 30-day readmissions in a neurosurgical patient population in order to identify patients at high-risk for readmission. Using this information, we implemented a new practice parameter with the goal of reducing preventable readmissions. METHODS: Patient characteristics and causes for readmission were prospectively collected for all neurosurgical patients readmitted to an academic medical center within 30 d of discharge between July and October 2018. A program was then initiated where postoperative neurosurgical spine patients were contacted by phone at standardized intervals before their 2-wk follow-up appointment, with the purpose of more quickly addressing surgical concerns and/or coordinating care for general medical issues. Finally, 30-d readmission rates were compared between the initial 4-mo period and January 2019 through April 2019. RESULTS: Prior to intervention, the largest group of readmitted patients included those who had undergone recent spinal surgery (16/47, 34%). Among spine readmissions during this time, 47% were readmitted before their two-week follow-up appointment, 67% lived over 50 miles from the medical center, and 40% were Medicare-insured. There was a statistically significant difference in the mean rate of spine readmissions per month in the periods before (7.0%) and after (3.0%) the program onset ( P = .029, 57% decline). The total number of surgically and medically related spine readmissions decreased between the pre- and postintervention periods from 10 to 3 (70%) and 3 to 1 (67%), respectively. CONCLUSION: Our data suggests that a large number of neurosurgical readmissions may be prevented by the simple process of early follow-up and consistent communication via telephone. Readmission rates may be further reduced by standardizing the coordination of postoperative general medical follow-up and providing thorough wound care teaching for high-risk patients.